2012
DOI: 10.1016/j.jhazmat.2011.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of compost addition on lead and arsenic bioavailability in reclaimed orchard soil assessed using Porcellio scaber bioaccumulation test

Abstract: A long history of lead arsenate application in orchards has led to significant accumulation of Pb and As in the topsoil. Besides the threat that such soils represent for the environment, reclamation of old orchards for agricultural purposes implies the exposure of humans to Pb and As. In this study we assessed the influence of vegetable compost addition (as a sustainable agricultural practice) to contaminated acidic orchard soil on Pb and As bioavailability, assessed with two selective non-exhaustive chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 57 publications
(58 reference statements)
1
21
0
Order By: Relevance
“…In contrast, neither of the compost amendments showed an ability to reduce As concentrations in the redworm tissues (p= 0.810). These earthworm bioassay results show a similar trend in the effects of compost to a related woodlice ( Porcellio scaber , L.) bioassay conducted on the same orchard soils, in which the BAF for As was generally greater than that for Pb, and compost amendment decreased Pb but increased As bioavailability (Udovic and McBride, 2012). …”
Section: Resultssupporting
confidence: 57%
“…In contrast, neither of the compost amendments showed an ability to reduce As concentrations in the redworm tissues (p= 0.810). These earthworm bioassay results show a similar trend in the effects of compost to a related woodlice ( Porcellio scaber , L.) bioassay conducted on the same orchard soils, in which the BAF for As was generally greater than that for Pb, and compost amendment decreased Pb but increased As bioavailability (Udovic and McBride, 2012). …”
Section: Resultssupporting
confidence: 57%
“…It is well-known that total soil Cd concentrations tend to be a poor proxy for predicting Cd mobility, solubility, extractability, and bioavailability (Udovic and McBride 2012). This is because the total sum of all chemical forms of Cd are rarely 100 % bioavailable (Udovic and McBride 2012), and the biogeochemical behavior of Cd depends largely on the free Cd concentration (Dabrin et al 2012).…”
Section: Bioavailability Of CD In Soilmentioning
confidence: 99%
“…It is well-known that total soil Cd concentrations tend to be a poor proxy for predicting Cd mobility, solubility, extractability, and bioavailability (Udovic and McBride 2012). This is because the total sum of all chemical forms of Cd are rarely 100 % bioavailable (Udovic and McBride 2012), and the biogeochemical behavior of Cd depends largely on the free Cd concentration (Dabrin et al 2012). For these reasons, knowledge of Cd speciation is considered necessary for informing soil remediation and risk assessment studies (Niazi et al 2011b;Shahid et al 2011Shahid et al , 2012aBade et al 2012 Traditionally, analytical techniques used to assess metal speciation in soil and water have included anodic stripping voltammetry, ion selective electrodes, competitive ligand equilibration/adsorptive stripping cathodic voltammetry, and sorption onto C 18 columns (Cobelo-García et al 2005).…”
Section: Bioavailability Of CD In Soilmentioning
confidence: 99%
“…A similar increase in Cu has occurred in citrus orchards and avocado orchard soils with an established history of copperbased fungicide use, with current concentrations ranging between 110 and 1500 mg kg À1 Cu (Fan et al, 2011;Merrington et al, 2002). Several studies in other countries have shown that substantial quantities of Pb and As may accumulate in orchard topsoils as a result of repeated lead arsenate application (Pendergrass and Butcher, 2006;Udovic and McBride, 2012;Hood, 2006).…”
Section: Introductionmentioning
confidence: 99%